The Influence Of Financial Literacy, Financial Efficacy And Demographic Factors On Investment Decisions In The Capital Market - Khaerunnisa Khaerunnisa; Andi Rustam; Rustan Rustan (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine the effect of financial literacy, financial efficacy and demographic factors on student investment decisions in the capital market. This type of research is quantitative using a questionnaire as a source of data collection. This study uses the slovin method using multiple linear analysis techniques using the SPSS application. The results showed that financial literacy has a positive and significant effect on student decisions in the capital market, meaning that the better financial literacy, the better student investment decisions in the capital market. Financial efficacy has a positive and significant effect on student investment decisions in the capital market, meaning that the better the financial efficacy, the better the student investment decisions in the capital market. Demographic factors have a positive and significant effect on student investment decisions in the capital market, meaning that the better the demographic factors, the better the student investment decisions in the capital market.